The expanding world of OAI.(Open Archives Initiative Protocol for Metadata Harvesting, OAI-PMH) - Tennant, Roy (Library Journal, 2004)
More importantly, the service is based on the concept of Extensible Repository Resource Locators (ERRoLs) for OAI Identifiers. ERRoLs are URLs that can link to any metadata record or web resource related to supported OAI repositories. This means that by going through the OCLC OAI resolver service at errol.oclc.org, any OAI-PMH capability (e.g., retrieve record) can be made actionable by a simple URL. OCLC is even offering an RSS feed for metadata from any registered OAI-compliant repository.